Volume 3C: General 1993
DOI: 10.1115/93-gt-342
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of the Nitrous Oxide Pathway to NOx in Lean-Premixed Combustion

Abstract: This study addresses the importance of the different chemical pathways responsible for NOx formation in lean-premixed combustion, and especially the role of the nitrous oxide pathway relative to the traditional Zeldovich pathway. NOx formation is modeled and computed over a range of operating conditions for the lean-premixed primary zone of gas turbine engine combustors. The primary zone, of uniform fuel-air ratio, is modeled as a micro-mixed well-stirred reactor, representing the flame zone, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 10 publications
2
27
0
Order By: Relevance
“…However, Reisel and Laurendeau (1994j' possibly explaining this result. Nicol et al (1993) found that pressure does affect NO production when they modeled lean, premixed CHJair combustion using three different reaction mechanisms (including the GMK-DB mechanism). They found a weak relationship between NO formation and pressure for lean flames (0.5~r/>~0.7) at pressures up to 10 atm, though the dependence varied with the reaction mechanism, equivalence ratio and pressure.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…However, Reisel and Laurendeau (1994j' possibly explaining this result. Nicol et al (1993) found that pressure does affect NO production when they modeled lean, premixed CHJair combustion using three different reaction mechanisms (including the GMK-DB mechanism). They found a weak relationship between NO formation and pressure for lean flames (0.5~r/>~0.7) at pressures up to 10 atm, though the dependence varied with the reaction mechanism, equivalence ratio and pressure.…”
Section: Resultsmentioning
confidence: 98%
“…Correa and Smooke (1990) also found that NO x is insensitive to pressure in their modeling of lean, premixed laminar CH./air flames. However, in a recent study by Nicol et al (1993),enhanced NO formation was found for lean, premixed flames when using a simple gas-turbine model composed of a wellstirred reactor followed by a series of plug-flow reactors. Despite investigating the importance of various NO formation pathways for several different reaction mechanisms as a function of pressure, no conclusive relationship could be developed between predicted NOx emissions and pressure at 1-30 atm.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…In particular, most studies have calculated the NO mole fraction with the full mechanism and compared this to the NO formed by eliminating one pathway at a time from the full mechanism (for example, Nicol et al, 1995). This procedure does not account for the competitive paths connecting the various pathways.…”
Section: Aiche Journalmentioning
confidence: 98%
“…iN Emissions Variables affecting the production of NO. have been extensively studied by Nicol et. al.…”
Section: )mentioning
confidence: 99%